PENERAPAN MANAJEMEN SAINS DAN TEKNOLOGI DI SEKOLAH MENENGAH PERTAMA ISLAM CENDEKIA CIANJUR: THE IMPLEMENTATION OF SCIENCE AND TECHNOLOGY MANAGEMENT IN CIANJUR ISLAMIC JUNIOR HIGH SCHOOL - Nurmaulida, Winda; Irawan; Priatna, Tedi (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2023)
To achieve its main objectives, management is a methodical and disciplined effort aimed at harmonizing Planning, Organization, locomotion, organization and evaluation. SMP Islam Cendekia Cianjur, a contemporary Islamic boarding school that is transforming through the digitization of schools to keep up with the progress of national and international education, is the location of this research. This study aims to clarify how science and Technology Management is applied in junior high schools that have an Islamic Foundation. This study uses descriptive-analytical methodology and qualitative approach. Information about the elements that help and hinder the achievement of Science and Technology Management in SMP Islam Cendekia Cianjur was collected through observation, interviews, and documentation. The results show that teachers, students and teaching staff still need a lot of help when it comes to the use of technology platforms in the classroom in terms of Science and Technology Management. As a result, regular training for Human Resources is required.